Addition of Lubiprostone to polyethylene glycol(PEG) enhances the quality & efficacy of colonoscopy preparation: a randomized, double-blind, placebo controlled trial. Issue 1 (December 2016) - Banerjee, Rupa; Chaudhari, Hrushikesh; Shah, Nirish; Saravanan, Arjunan; Tandan, Manu; Reddy, D.
Abstract Background Adequate bowel preparation is an essential prerequisite for complete mucosal visualization during colonoscopy. Polyethylene glycol (PEG) solutions are commonly used. However the large volume of the solution is often poorly tolerated. Addition of Lubiprostone (LB) could improve the adequacy of standard PEG preparation & reduce requirement. The aims to assess adequacy of PEG preparation with addition of single dose LB (24mcg) vs placebo and efficacy of reduced dose PEG + LB compared with full dose PEG + LB. Methods Single center prospective double blind randomized controlled trial. Part I: 442 patients for colonoscopy randomized to receive placebo (GrA) or single dose of LB (GrB) prior to PEG preparation. Quality of bowel preparation graded 0–9 according to Boston Bowel Preparation Scale (BBPS). BBPS-9: excellent and BBPS 0–4: repeat procedure. Part II: 146 patients randomized to receive LB + 1.5 L PEG (GrC; 75) or LB + 1 L PEG (GrD; 71). BBPS score compared with GrB (2 L PEG). Results Part I: 442 patients (221 GrA & 221 Gr B). LB resulted in significant improvement in total BBPS (7.44 + 0.14 vs. 6.36 + 0.16, p < 0.0001). 66.5 % Gr B vs 38 % Gr A had excellent prep; 42.5 % GrB vs 24 % GrA had adequate prep. Repeat procedure needed 9.5 % Gr B vs 16.7 % Gr A (P < 0.01). Part II: No difference in BBPS scores with lower doses (Gr C&D) compared to standard (GrB) (Mean BBPS 7.44 + 0.14 GrA, 7.30 + 0.25 GrC;7.25 + 0.26 GrD;p >0.05). Conclusion Single dose LB prior to PEG significantly enhanced bowel preparation compared to PEG alone. There was no significant difference in quality of preparation with lower doses of PEG when combined with LB. Trial registration The study protocol was approved by institutional review board and the trial was registered on March 22, 2011 with clinicaltrials.gov (NCT01324284 ).